Inactivation of the Prolyl Isomerase Pin1 Sensitizes BRCA1-Proficient Breast Cancer to PARP Inhibition - Luo, Man-Li (Cancer Res, 2020)
PARP inhibitor monotherapies are effective to treat patients with breast, ovary, prostate, and pancreatic cancer with BRCA1 mutations, but not to the much more frequent BRCA wild-type cancers. Searching for strategies that would extend the use of PARP inhibitors to BRCA1-proficient tumors, we found that the stability of BRCA1 protein following ionizing radiation (IR) is maintained by postphosphorylational prolyl-isomerization adjacent to Ser1191 of BRCA1, catalyzed by prolyl-isomerase Pin1. Extinction of Pin1 decreased homologous recombination (HR) to the level of BRCA1-deficient cells. Pin1 stabilizes BRCA1 by preventing ubiquitination of Lys1037 of BRCA1. Loss of Pin1, or introduction of a BRCA1-mutant refractory to Pin1 binding, decreased the ability of BRCA1 to localize to repair foci and augmented IR-induced DNA damage. In vitro growth of HR-proficient breast, prostate, and pancreatic cancer cells were modestly repressed by olaparib or Pin1 inhibition using all-trans retinoic acid (ATRA), while combination treatment resulted in near-complete block of cell proliferation. In MDA-MB-231 xenografts and triple-negative breast cancer patient-derived xenografts, either loss of Pin1 or ATRA treatment reduced BRCA1 expression and sensitized breast tumors to olaparib. Together, our study reveals that Pin1 inhibition, with clinical widely used ATRA, acts as an effective HR disrupter that sensitizes BRCA1-proficient tumors to PARP inhibition. SIGNIFICANCE: PARP inhibitors have been limited to treat homologous recombination–deficient tumors. All-trans retinoic acid, by inhibiting Pin1 and destabilizing BRCA1, extends benefit of PARP inhibitors to patients with homologous recombination–proficient tumors.